TRANSLATION STRATEGY ON "LET IT GO" SONGS THAT WAS SUNG BY IDINA MENZEL WITH INDONESIAN VERSION - Hendra Hendra (Journal of English Language Teaching and Literature (JELTL), 2019)
The purpose of this research is to analyze the translation strategy at the word level used in the translation of the song in the animated movie "Let it go" from English into Bahasa Indonesia. The frequency with which each translation strategy is measured. The translation strategy for addressing disparate words at Word level proposed by Baker (1992) is applied as a framework for data analysis. The data for this study is the lyrics of the original song "Let it go" sung by Idina Menzel in the original movie produced by Walt Disney "Frozen" with a translation version of Indonesian. The result shows that the seven strategies proposed by Baker (1992), identified as used in this study. Translation strategiesare translated by disappearances, translated by paraphrasing using unrelated words, and translations by cultural substitution.